A Review of Kant’s Groundwork of the Metaphysics of Morals: A Reader’s Guide - Yassaman Hoshyar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Groundwork of the Metaphysics of Morals is one of the most influential ethical books and, at the same time, it is one of the most difficult ones, and every commentary on Kant’s ethical theory, at the first step, concentrates on this book. Kant’s Groundwork of the Metaphysics of Morals: A Reader Guide which has been written by Professor Paul Guyer is an authentic commentary and is recently translated into Persian. With respect to the role of Guyer in recent Kant’s studies as a leading scholar, this book has a high position. In this article, besides a general review of these two books in terms of their importance in Persian and English literature and editorial features and translation of Guide, Guyer’s expression of Kant’s arguments, and significant and influential points of Guide are reviewed. These points give readers a good insight into understanding Kant’s moral theory and avoiding ambiguities and objections. In addition, in some points, the Guide is compared with other commentaries on Groundwork, especially with Timmermann’s and evaluated.